Pre-transplant residual diuresis and oxalic acid concentration influence kidney graft survival - Gideon Post Hospers; Mirjam Laging; Wesley J. Visser; Pedro Miranda Afonso; Jeroen GHP Verhoeven; Ingrid RAM Mertens zur Borg; Dennis A. Hesselink; Anneke M.E. de Mik-van Egmond; Michiel G.H. Betjes; Madelon van Agteren; David Severs; Jacqueline van de Wetering; et al. (PLoS ONE, 2025)
Background and hypothesis Oxalic acid, a toxic metabolic end product, accumulates when kidney function deteriorates. Apart from its direct tubulotoxicity, it crystallizes at concentrations above 30–40 µmol/L. High oxalic acid concentrations at transplantation might negatively influence kidney transplant function. The influence of the concentrations of oxalic acid and its precursors and residual diuresis on kidney transplant outcomes was studied. Methods In this prospective cohort study, patients who received a kidney transplant between September 2018 and January 2022 participated. Concentrations of oxalic acid and precursors were determined in pre-transplant blood samples. Data on residual diuresis and other recipient, donor or transplant related variables were collected. Follow-up lasted until July 1st 2023. Results 496 patients were included, 154 were not on dialysis. Median residual diuresis was 1000 mL/day (IQR 200; 2000 mL/day). There were 230 living donor transplantations. Oxalic acid concentrations exceeded the upper normal concentration in 99% of patients, glyoxylic acid in all patients. There were 52 (10%) graft failures. As the influence of oxalic acid on the risk of graft failure censored for death was non-linear, it was categorized into two groups: ≤ 60 and > 60 μmol/L. In multivariable Cox analysis the graft failure censored for death risk was significantly influenced by residual diuresis, donor type (living versus deceased), donor age and oxalic acid. In 180 patients oxalic acid concentration shortly after transplantation was significantly lower than pre-transplant concentrations, suggesting excretion by the new graft. A better eGFR at day 7 was associated with lower oxalic acid concentration. Oxalic acid and residual diuresis did not influence patient survival. Conclusion Residual diuresis and oxalic acid concentration are important and independent predictors of graft survival censored for death. These results underline the importance of pre-emptive transplantation, or optimizing the pre-transplant patients’ condition regarding waste product concentrations.